Sosialisasi Pentingnya Manajemen Keuangan Personal Tenaga Pendidik SD Negeri No. 104274 - Hanna Meilani Damanik; Martin Luter Purba; Hendrik E.S Samosir; Nancy Nopeline (LPPM Universitas HKBP Nommensen, 2022)
This activity aims to help teachers at SD Negeri No. 104274 Pematang Kasih, Pantai Cermin District, Serdang Regency understands the importance of personal financial planning as well as practical things and basic principles that can be carried out in the context of these activities. Activities carried out in the form of lectures or seminars attended by 20 teachers at the school. Through this activity, it is hoped that it can provide benefits where teachers have a new understanding of the importance of financial planning process, understanding financial goals at every phase of life, financial planning life cycle, personal finance principles in planning